Kinetics and localisation of haemin-induced lipoprotein oxidation - Noppawan Phumala Morales (2020)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. Haemin (iron (III)-protoporphyrin IX) is a degradation product of haemoglobin in circulating erythrocytes. Haemin may play a key oxidising agent for lipoprotein oxidation in patients with haemolytic anaemia. In this study, kinetic changes in chemical composition and target sites of haemin-induced LDL and HDL oxidation were investigated. Haemin initially induced the loss of α-tocopherol, followed by accumulation of lipid hydroperoxide (LP) and alteration of core lipid fluidity. The absence of LP in HDL was explained by the antioxidant activity of PON in addition to α-tocopherol. The target site of haemin was evaluated by ESR spin labelling with 5- and 16-doxyl steric acids. In the presence of t-BuOOH and haemin, ESR signal decay of the doxyl moiety demonstrated the initiation phase and the propagation phase of lipid peroxidation. The results of the lag time and the rate of signal decay indicated that haemin is located near the 16th carbon atom of the fatty acid chain in the phospholipid layer. The analyses of motion parameters, order parameter (S) of 5-DS and rotational correlation time (τ) of 16-DS, supported the observation that the lipid properties changed near the hydrophobic region rather than at the surface region of lipoproteins. Moreover, ESR spin labelling demonstrated that haemin molecules but not iron ions caused lipoprotein oxidation. In conclusion, haemin is a potent inducer of lipoprotein oxidation, and the target site for this oxidation is near the hydrophobic core of the lipoprotein leading to the loss of antioxidant activities and changes in lipid composition and physical properties.